1977
DOI: 10.1002/jlac.197719770902
|View full text |Cite
|
Sign up to set email alerts
|

Cycloadditionen mit Azabenzolen, XI. Cycloadditionen mit Methoxy‐ und Dialkylamino‐1,2,4‐triazinen

Abstract: Die Methoxy-l,2,4-triadne 2a-2c und 11 sowie das 3-Dimethylamino-l,2,4-triazin (2e) reagieren mit dem elektronenreichen Dienophil N,N-Diethyl-1 -propinylamin (3) im Sinne einer [4 + 21-Cycloaddition. 1,2,4-Triazine 2g-2 j mit 2 oder 3 Dialkylaminogruppen lassen sich dagegen mit dem elektronenarmen Dienophil AcetylendicarbonsBure-dimethylester (1) im Sinne einer [4 + 21-Cycloaddition umsetzen. Cydoaddition Reactions with Azabenzenes, MI). -Cycloaddition Reactioos with Methoxyand Dialkylamino-l,2,4-triaziies The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The preparation of annulated pyridine derivatives by the inverse electron demand Diels-Alder Scheme 1 (IDA) reaction of monomeric 1,2,4-triazines is a well establish tactic in organic synthesis. 14 With the exception of one isolated example, 15 however the IDA reactions of dimeric 1,2,4-triazines with electron-rich dienophiles have not been studied in detail. Here we present a full account of this work and of our recent findings, 16 on the regioselectivity of the Diels-Alder reaction between functionalized 5,5¢-bi-1,2,4-triazines 2a,b and cyclic or linear enamines 3a-e, leading to a series of symmetrical or unsymmetrical cycloalkeno [c]fused 2,2¢-bipyridines.…”
mentioning
confidence: 99%
“…The preparation of annulated pyridine derivatives by the inverse electron demand Diels-Alder Scheme 1 (IDA) reaction of monomeric 1,2,4-triazines is a well establish tactic in organic synthesis. 14 With the exception of one isolated example, 15 however the IDA reactions of dimeric 1,2,4-triazines with electron-rich dienophiles have not been studied in detail. Here we present a full account of this work and of our recent findings, 16 on the regioselectivity of the Diels-Alder reaction between functionalized 5,5¢-bi-1,2,4-triazines 2a,b and cyclic or linear enamines 3a-e, leading to a series of symmetrical or unsymmetrical cycloalkeno [c]fused 2,2¢-bipyridines.…”
mentioning
confidence: 99%
“…Triazines are sufficiently reactive to participate in [4+ 2] cycloaddition reactions with typical electron-deficient dienophiles. The additional substitution of the 1,2,4-triazine nucleus with strong electron-donating substituents (-OCH3, -NMe2) increases its rate of participation in normal (HOMOdiene-controlled) Diels-Alder reacitons, eq30.82'83 This additional subthe 1,2,4-triazine nucleus with electrondonating substituents does not preclude the ability of the 1,2,4-triazine to participate in [4+ 2] cycloaddition processes with electron-rich dienophiles including ynamines 82. Recent studies have explored and confirmed the utility of the intramolecular Diels-Alder reactions of alkyne 1,2,4-triazines, eq 31,84 and reports of the use of heterodienophiles, amidines85® and aldehyde N,N-dimethyl hydrazones,8611 in [4 + 2] cycloaddition processes with 1,2,4-triazines have been detailed, eq 32.XIV 1,2,4,5-Tetrazines Since the initial report of symmetrical perfluoroalkyl 1,2,4,5-tetrazines participating in [4 + 2] cycloaddition reactions with representative olefins in a study which constituted the first demonstration of the viability of the inverse electron demand Diels-Alder reaction,11…”
mentioning
confidence: 99%
“…Thanks to [4+2]/retro‐[4+2] sequences with ynamines, 1,2,4‐triazines 70 and 73 can give either pyrimidines [through an “N2C5 preference”; Scheme , Equation (1)] or pyridines such as 75 [through a “C3C6 preference”; Equation (2)] . As one might anticipate, the regiochemistry of the initial cycloaddition step is not clear cut, and mixtures of cycloadducts are often obtained depending on the nature and positions of the triazine's substituents.…”
Section: [4+2] Cycloadditions Of Ynaminesmentioning
confidence: 99%